Comprehensive TCM treatments combined with chemotherapy for advanced non-small cell lung cancer: A randomized, controlled trial. Issue 18 (7th May 2021) - Xiao, Zhiwei; Chen, Zhiqiang; Han, Rui; Lu, Liming; Li, Zeyun; Lin, Jietao; Hu, Leihao; Huang, Xuewu; Lin, Lizhu
Abstract: Objective: We conducted this study to evaluate the efficacy and safety of traditional Chinese medicine (TCM) in advanced non-small cell lung cancer (NSCLC) patients who underwent chemotherapy. Design: This was a prospective, open-label, randomized controlled trial. NSCLC patients at stage IIIA, IIIB, or IV were randomly assigned to either TCM plus chemotherapy or chemotherapy alone. The comprehensive TCM treatment consisted of Kang Ai injection, herbal decoction, and Zhenqifuzheng capsules. The primary endpoint was quality of life (QOL) measured by the Functional Assessment of Cancer Therapy-Lung version 4.0. The secondary endpoints were chemotherapy completion rate, tumor response, and adverse events. All assessments were done at baseline, the third week, and the sixth week. Results: Thirty-nine participants were randomly assigned to the treatment group and 36 to the control group. The QOL scores were significantly improved in the treatment group compared with those of the control group in social well-being (cycle 1, P = .048; cycle 2, P = .015), emotional well-being (cycle 1, P = .047; cycle 2, P = 4.29E-05), and functional well-being (cycle 1, P = .030; cycle 2, P = .003), while the QOL scores in the above 3 domains declined in the control group ( P < .05). Both groups had a decline in the physical well-being score (cycle 1, P = .042; cycle 2, P = .017) and lung cancer symptom score (cycle 1, P = .001; cycle 2, P = .001) after 2 courses of intervention. The deterioration in physical well-being and lung cancer symptoms was noticeably smaller in the treatment group ( P < .05). There were significant differences between the 2 groups in social well-being, emotional well-being, functional well-being, lung cancer symptom domain, and the total score ( P < .05). Patients in the treatment group had a significantly lower incidence of platelet reduction than the control group ( P = .028) after 2 cycles of treatment. No significant difference in nonhematological adverse events (AEs) was observed. Conclusion: This study illustrated that comprehensive TCM treatment could promote the QOL of NSCLC patients, alleviate symptoms, and reduce the AEs caused by chemotherapy, verifying the synergistic and attenuating effects of TCM in NSCLC patients undergoing chemotherapy. Trial registration: Chinese Clinical Trial Registry (www.chictr.org.cn ): ChiCTR-TRC-13003637